PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN DAN PERKEBUNAN KABUPATEN BIMA - Yustika Karunia; Nurhayati Nurhayati (Jurnal Bina Bangsa Ekonomika, 2022)
In government agencies, human resources are needed that can support a system in the organization, which makes the driver for the organization to advance in the era of global competition, not only technology plays an important role to be developed but performance that is a benchmark for the success of agencies in creating quality human resources. One of the good supports for employee performance is organizational culture and work environment so that it can produce good performance. The purpose of this study is to determine the influence of organizational culture and work environment significantly and partially on performance in the Agriculture and Plantation Service of Bima Regency, as well as to determine the influence of organizational culture and work environment simultaneously on employee performance at the Bima Regency Agriculture and Plantation Service.While to analyze the data obtained, a Simple Correlation Coefficient Analysis was used,    Multiple Correlation Coefficient Analysis, Multiple Linear Regression Analysis, Determination Coefficient Analysis, and Hypothesis Test using Significance Test (t Test and F Test). The results showed that organizational culture had a positive and significant effect on employee performance at the Bima Regency Agriculture and Plantation Service, the work environment had a positive and significant effect on employee performance at the Bima Regency Agriculture and Plantation Service and organizational culture and work environment had a positive and significant simultaneous effect on employee performance at the Bima Regency Agriculture and Plantation Service